Baffin Island and adjacent regions to show unexplored areas / prepared by the American Geographical Society of New York - American Geographical Society of New York (New York : American Geographical Society of New York, 1926)
Shows "major area in need of exploration" and "routes of the Neptune 1903-1904."; "Oct. 1926."; Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography Color; 1:2,500,000